Spatial distribution of Pseudaletia sequax Franclemlont in triticale under no-till management (Scientia Agricola, 2006)
The knowledge of the spatial distribution of insect populations in crops allows the estimation of the population density in space, the classification of damage impact on yield as well as decisions to be made about control measures. To evaluate the spatial distribution of the wheat armyworm Pseudaletia sequax Franclemont, in relation to the development and yield of triticale (Triticum secale Wittmack) under no-till management, samplings were taken at 302 points in a square grid measuring 10 x 10 m, in Campinas, SP, Brazil. The caterpillar population was evaluated by counting their number per meter at the base of triticale plants. Grain yield (kg ha-1), cover of the above-ground part (kg ha-1), mean plant height (m), and ground cover percentage were evaluated after the triticale crop was mechanically harvested, with the measurement of the mass of straw left on soil surface. Geostatistics was used to analyze spatial variability, by means of semivariogram analysis, and interpolation of data by both ordinary and indicator kriging, considering the injury threshold level of ten caterpillars per square meter to construct isoline maps. Spatial dependence occurred for all variables, demonstrating an aggregate spatial distribution pattern of the caterpillar in triticale. Random sampling in this area would fail to reveal that grain yield was affected at the location with the greatest occurrence of the caterpillar. At that location, the economic injury level was exceeded, which would justify the adoption of control measures against the pest.